2017
DOI: 10.1007/s11211-017-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Recalling an Unfair Experience Reduces Adolescents’ Dishonest Behavioral Intentions: The Mediating Role of Justice Sensitivity

Abstract: Giovannelli declares that she has no conflict of interest. Maria Giuseppina Pacilli declares that she has no conflict of interest.Stefano Pagliaro declares that he has no conflict of interest. Carlo Tomasetto declares he has not conflict of interest. Manuela Barreto declares she has not conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…This supports both recent findings that perceived injustice in an educational context may have a significant impact on the lives of adolescents by potentially influencing dishonesty ( 62 ), and earlier studies showing that unfair treatment has implications for emotional states and behaviors ( 63 , 64 ). Research has observed that there are variations in sensitivity to unjust treatment ( 62 , 65 ), which may explain why this type is an overarching cause for some and not others. These findings, therefore, highlight that young people interpret events differently, but also demonstrate that young people may experience unfair treatment in comparison to their peers/sibling etc.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This supports both recent findings that perceived injustice in an educational context may have a significant impact on the lives of adolescents by potentially influencing dishonesty ( 62 ), and earlier studies showing that unfair treatment has implications for emotional states and behaviors ( 63 , 64 ). Research has observed that there are variations in sensitivity to unjust treatment ( 62 , 65 ), which may explain why this type is an overarching cause for some and not others. These findings, therefore, highlight that young people interpret events differently, but also demonstrate that young people may experience unfair treatment in comparison to their peers/sibling etc.…”
Section: Discussionsupporting
confidence: 89%
“…The second type, unfair treatment, highlights that, for some young people, what they interpret as unfair treatment may become the overarching cause of their emotional distress. This supports both recent findings that perceived injustice in an educational context may have a significant impact on the lives of adolescents by potentially influencing dishonesty (62), and earlier studies showing that unfair treatment has implications for emotional states and behaviors (63,64). Research has observed that there are variations in sensitivity to unjust treatment (62,65), which may explain why this type is an overarching cause for some and not others.…”
Section: Discussionsupporting
confidence: 87%
“…For people, the theory of BDT and previous studies have demonstrated humans can integrate social contextual information and personal information into decision‐making processes to adjust their responses toward inequity (Giovannelli et al, 2018 ; Nook et al, 2016 ; Peysakhovich et al, 2014 ). Extending findings to the social decision domain, our results suggest that previous unfair experience under the context of (dis)advantageous can alter personal third‐party responses to injustice.…”
Section: Discussionmentioning
confidence: 99%
“…Observer JS was positively related to disobeying an authority in order to be honest—particularly when the participants’ moral identity was also high—and to intervening despite physical danger in hypothetical scenarios (Sonnentag et al, 2018). Altruistic JS mediated the relation between recalling unfair events and lower willingness to behave dishonestly (Giovannelli et al, 2018).…”
Section: Justice Sensitivitymentioning
confidence: 99%